2017
DOI: 10.1136/bjophthalmol-2017-310258
|View full text |Cite
|
Sign up to set email alerts
|

Interdevice comparison of retinal sensitivity assessments in a healthy population: the CenterVue MAIA and the Nidek MP-3 microperimeters

Abstract: Retinal sensitivity measures higher, but luminance and contrast sensitivity measure lower for MAIA-generated values compared with the MP-3. The relationships, however, appeared fairly consistent, and application of a standard correction factor allowed the data to be inter-related, at least for normal eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 12 publications
2
31
0
Order By: Relevance
“…This outcome is consistent with that of À0.01 to À0.02 dB/year for microperimetry [40][41][42] and of À0.04 to À0.08 dB/year for SAP within 108. 15,17 In addition, the ranges of sensitivity values are consistent with those reported for ocular healthy individuals 43,44 and for those with AMD. 45,46 A limitation of the study is that the conclusion refers to those with AMD and warrants evaluation in visual field loss arising from other disease entities.…”
Section: Discussionsupporting
confidence: 85%
“…This outcome is consistent with that of À0.01 to À0.02 dB/year for microperimetry [40][41][42] and of À0.04 to À0.08 dB/year for SAP within 108. 15,17 In addition, the ranges of sensitivity values are consistent with those reported for ocular healthy individuals 43,44 and for those with AMD. 45,46 A limitation of the study is that the conclusion refers to those with AMD and warrants evaluation in visual field loss arising from other disease entities.…”
Section: Discussionsupporting
confidence: 85%
“…This finding confirms previous studies that the dynamic range of the system is limited particularly with regard to detection of slight mesopic retinal sensitivity loss. 11,25 Further improvements, such as the introduction of the MP-3 and other FCP devices, may overcome this limitation in the future.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Various studies have reported functional impairment in AMD patients beyond the reduction of best-corrected central visual acuity, including reading speed, low-luminance visual acuity, dark adaptometry, and fundus-controlled perimetry (FCP). [8][9][10][11][12] For the latter, early studies showed localized reduction of mesopic sensitivity over drusen and pigmentary changes. 13,14 Further developments of the MP-1S device (Nidek Technologies, Padova, Italy) led to the possibility of scotopic testing under dark-adapted conditions.…”
mentioning
confidence: 99%
“…The maximum luminance of the MP-3 is 10,000 asb, and the stimulus dynamic range is between 0 and 34 dB. [10][11][12][13][14] Only reliable test results (a false-positive rate of <20% and a false-negative rate of <25%) were used in the analyses, as in the HFV SITA test results set in the present study. A fixation loss is not applicable because the MP-3 has an autotracking system, making it possible to project the stimulus only at predefined retinal positions.…”
Section: Functional Dfr Angle Measurementmentioning
confidence: 99%
“…The novel MP-3 microperimeter (NIDEK Co., Ltd., Aichi, Japan) measures visual field sensitivity by projecting a target light directly onto the region of interest on the retina rather than onto a screen. 10,11 The retina position is automatically tracked and the stimulus location is aligned accordingly, resulting in precise determination of retinal test locations stimulated at each target presentation. Compared with the HVF test, this full-autotracking system makes it possible to measure sensitivities more accurately, at exact test points.…”
mentioning
confidence: 99%